Using eye-tracking to investigate patent examiners’ information seeking process - Loizides, Fernando; Diallo, Barrou (My University, 2014)
In this paper we present a methodology which was tested for using eye-tracking to record patent examiners’ visual attention during patent triage. The findings present ways that the eye-tracker can complement current metrics for evaluating information retrieval tools, as well as the ability to investigate further behaviors and actions which cannot be done by currently employed methods.
Keywords: Eye-tracking; Patent Examination; Patent Retrieval